ASSESSMENT OF IN VITRO EQUIVALENCE OF GENERIC DRUG BASED ON ALLOPURINOL IN TABLET FORM - ТАРАСЕНКО, Г. В.; ГУРКОВСЬКА, О. В.; БАУЛА, О. П.; САЛІЙ, О. О. (Technologies and Engineering, 2024)
Purpose. To study the dissolution kinetics of allopurinol-based solid dosage form and assess its equivalence under in vitro conditions compared to the generics medicinal product; to compare the similarity factor of dissolution profiles and evaluate the equivalence of the generic drug. Methodology: The pharmaceutical equivalence of the generic brand Allopurinol, 100 mg tablets, and the reference product Zyloric®, 100 mg tablets, by "Aspen Pharma GmbH" in Germany, was investigated. Analytical studies were conducted using the adsorption spectrophotometry method on a UV-1700 spectrophotometer "SHIMADZU" (Japan) and VK 7000 dissolution apparatus with a VK750D heater Vankel (USA). Analytical balances VR 221S from "Sartorius" (Switzerland) were utilized, along with a pH meter ADWA AD8000 (Hungary). Dissolution kinetics studies were carried out in accordance with the requirements of the State Pharmacopoeia of Ukraine (SPhU) 2.9.3 "Dissolution Test for Solid Dosage Forms, Guidelines on Bioavailability and Bioequivalence Studies, and WHO Guidelines. The studies were conducted in three buffer solutions at pH values of 1.2 (hydrochloric acid solution), 4.5 (acetate buffer solution), and 6.8 (phosphate buffer solution). Buffer solutions were prepared according to SPhU (2.9.3). The dissolution kinetics were conducted under specific conditions using the Vankel VK 7000 apparatus with a paddle (rotation speed 50 rpm), the dissolution medium volume at 900 ml and the dissolution medium temperature at 37±1°C. Samples was withdrawn manually using a 5 ml pipette from a zone midway between the surface of the dissolution medium and the rotating paddle 1 cm away from the vessel wall, at time intervals of 10, 15, 20, 30, and 45 minutes. Collected samples were subsequently filtered through an "Agilent" syringe filter (0.45 μm). After sample collection, the withdrawn volume was adjusted with the corresponding dissolution medium, and the pH of buffer solutions was monitored. Statistical analysis of the results was performed using Microsoft Office Excel with a confidence level of P=95%. To ensure statistically reliable results, the determination was conducted on 12 samples for each of the investigated objects. Findings. The equivalence assessment of the generic allopurinol-based drug in tablet form 100 mg was conducted by studying the dissolution kinetics through the "Biowaiver" procedure in accordance with the requirements of the ST-N MOZU 42-7.4:2022 "Medicinal Products. Bioequivalence Studies" and WHO recommendations. It was found that in a medium with pH 1.2 (hydrochloric acid), the release fraction of the active substance from the analyzed drug was 94.37% within a 15-minute timeframe. Additionally, in the medium with pH 4.5 (acetate buffer solution) and pH 6.8 (phosphate buffer solution), the release fraction of the active substance was 64.66% and 84.17%, respectively. Thus, the dissolution kinetic curves (dissolution profiles) of the generic and reference drugs in the investigated media were similar, and the medicinal products were considered "rapid". The similarity factors of dissolution profiles for the generic drug at pH 1.2, 4.5, and 6.8 were 61.12, 58.25, and 91.07, respectively, confirming the similarity of dissolution profiles to the reference drug since the similarity factor f2 > 50. Originality. The equivalence assessment of the generic allopurinol-based drug in tablet form was conducted in vitro for the first time, confirming the similarity of dissolution profiles through the "Biowaiver" procedure. Practical value. Equivalence of the generic and reference allopurinol-based drugs has been confirmed through the study of the release kinetics of the active substance and the comparison of dissolution profiles in vitro. The obtained results allow to confirm the equivalence of the investigated drugs without the need for in vivo bioequivalence studies.